THE ANALYSIS OF TEACHER’S STRATEGIES TOWARD SPEAKING SKILL IN SECONDARY SCHOOL - Latifatul Masintan Masintan; St. Shabibatul Rohmah Rohmah; Triana Kartika Santi Santi (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2024)
This research was conducted to analysis the teaching strategy towardstudents’ speaking skill. The aims of this research is to know the strategiesof teacher during teaching and learning process and know step by step ofteacher did by using teaching strategy toward speaking skill. By usingqualitative approach, source information for teaching strategy researchinclude questionnaire, lesson plan and speaking students’ scoring from36 EFL students were aged 15 to 16 and 2 English teacher were aged 25-28 of rural background condition in one of secondary school inBanyuwangi, East Java. The findings reveal that the teacher used teachingstrategy (games, role play and group investigation) during Englishlearning process. The findings also confirm that, the students got goodincreasing in speaking skill an the teacher used the different steps to applythe teaching strategy.